An Enantiopure Cyclometallated Iridium Complex Displaying Long‐Lived Phosphorescence both in Solution and in the Solid State. Issue 4 (21st March 2019) - Macé, Aurélie; Hellou, Nora; Hammoud, Joanna; Martin, Clothilde; Gauthier, Etienne S.; Favereau, Ludovic; Roisnel, Thierry; Caytan, Elsa; Nasser, Ghassan; Vanthuyne, Nicolas; Williams, J. A. Gareth; Berrée, Fabienne; et al.
Abstract: A new enantiopure cyclometallated iridium complex bearing a [4]helicenic : C ∧ C - ‐coordinating and two : N ∧ C - ‐coordinating dfppy (2‐(2, 4‐difluorophenyl)‐pyridyl) ligands was prepared. This complex displayed long‐lived phosphorescence both in solution and in the solid state. Its chiroptical properties, namely electronic circular dichroism and circularly polarized luminescence, were also examined. Comparison with former chiral complexes enabled assignment of the ΔIr ‐(−) and ΛIr ‐(+) absolute configurations. Abstract :